Ginseng Gintonin Attenuates Lead-Induced Rat Cerebellar Impairments during Gestation and Lactation - Sung Min Nam (Biomolecules, 2020)
Gintonin, a novel ginseng-derived lysophosphatidic acid receptor ligand, improves brain functions and protects neurons from oxidative stress. However, little is known about the effects of gintonin against Pb-induced brain maldevelopment. We investigated the protective effects of gintonin on the developing cerebellum after prenatal and postnatal Pb exposure. Pregnant female rats were randomly divided into three groups: control, Pb (0.3% Pb acetate in drinking water), and Pb plus gintonin (100 mg/kg, p.o.). Blood Pb was increased in dams and pups; gintonin treatment significantly decreased blood Pb. On postnatal day 21, the number of degenerating Purkinje cells was remarkably increased while the number of calbindin-, GAD67-, NMDAR1-, LPAR1-immunoreactive intact Purkinje cells, and GABA transporter 1-immunoreactive pinceau structures were significantly reduced in Pb-exposed offspring. Following Pb exposure, gintonin ameliorated cerebellar degenerative effects, restored increased pro-apoptotic Bax, and decreased anti-apoptotic Bcl2. Gintonin treatment attenuated Pb-induced accumulation of oxidative stress (Nrf2 and Mn-SOD) and inflammation (IL-1β and TNFα,), restoring the decreased cerebellar BDNF and Sirt1. Gintonin ameliorated Pb-induced impairment of myelin basic protein-immunoreactive myelinated fibers of Purkinje cells. Gintonin attenuated Pb-induced locomotor dysfunctions. The present study revealed the ameliorating effects of gintonin against Pb, suggesting the potential use of gintonin as a preventive agent in Pb poisoning during pregnancy and lactation.